Prevalence of Chronic Kidney Disease Among Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study in Pakistan - TARIQ, AYESHA; YOUNAS, MALAIKA; NAWAZISH, FILZA; SADAF, RIMSHA; HAMAD, MAAZ; ABDULLAH, HAFIZ HAMMAD (Pakistan Journal of Medical & Health Sciences, 2025)
Background: chronic kidney disease (CKD) is one of the most serious complications of type 2 diabetes mellitus (T2DM). Pakistan, with one of the highest global burdens of diabetes, faces an increasing prevalence of diabetic kidney disease, yet data remain scarce. Early detection using estimated glomerular filtration rate (eGFR) and urine albumin–creatinine ratio (ACR) is essential for timely intervention. Objectives: To determine the prevalence and stages of CKD among T2DM patients in Pakistan and to identify associated demographic and clinical risk factors. Methods: This cross-sectional study was conducted at Sargodha Medical College, Sargodha and The University of Lahore Teaching Hospital, Lahore from June 2024 to February 2025. A total of 70 adults with T2DM were enrolled consecutively. Demographics, comorbidities, and treatment history were recorded. Serum creatinine was measured to calculate eGFR using the CKD-EPI 2021 equation, and urine ACR was assessed to detect albuminuria. CKD was defined according to KDIGO 2024 criteria as eGFR <60 mL/min/1.73 m² and/or ACR ≥30 mg/g, with chronicity confirmed through past results or repeat testing. Results: The mean age of participants was 55.7 ± 10.8 years, with 54.3% males. The mean diabetes duration was 9.2 years, and 65.7% had hypertension. Poor glycemic control (HbA1c ≥8%) was observed in 55.7%. Overall, 31.4% (22/70) had CKD. Among them, 8 were in stage G3a, 6 in G3b, and 3 in G4, while 17 patients (24.3%) had albuminuria (10 in A2, 7 in A3). CKD was more frequent in older patients, those with longer diabetes duration, hypertension, and poor glycemic control. Conclusion: CKD affects nearly one-third of diabetic patients in Pakistan, with many cases detectable only through albuminuria screening. Routine use of both eGFR and ACR, alongside aggressive management of blood pressure and glycemia, and broader access to renoprotective therapies are essential to reduce the burden of diabetic kidney disease.